2020
DOI: 10.1039/d0pp00082e
|View full text |Cite
|
Sign up to set email alerts
|

Interplay among the “flipping” glutamine, a conserved phenylalanine, water and hydrogen bonds within a blue-light sensing LOV domain

Abstract: A combined photoacoustics and molecular dynamics approach highlights the crucial role of a conserved phenyalanine in photosensing LOV domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…[50] The net result is ordering of the N/C-termini and formation of a light-dependent salt-bridge between Arg125-Glu158. We note that the observed allosteric process is directly analogous to recent computational studies of YtvA, [24] where they observed coupling between Gln conformational dynamics and light-dependent movement of a Phe residue equivalent to Phe66 (Phe46 in YtvA). These observations raise the possibility of a Gln-independent signaling PLOS COMPUTATIONAL BIOLOGY mechanism that relies on Phe movement in response to changes in flavin electronics.…”
Section: Proximal Signaling Event and A Gln-less Mechanismsupporting
confidence: 83%
See 3 more Smart Citations
“…[50] The net result is ordering of the N/C-termini and formation of a light-dependent salt-bridge between Arg125-Glu158. We note that the observed allosteric process is directly analogous to recent computational studies of YtvA, [24] where they observed coupling between Gln conformational dynamics and light-dependent movement of a Phe residue equivalent to Phe66 (Phe46 in YtvA). These observations raise the possibility of a Gln-independent signaling PLOS COMPUTATIONAL BIOLOGY mechanism that relies on Phe movement in response to changes in flavin electronics.…”
Section: Proximal Signaling Event and A Gln-less Mechanismsupporting
confidence: 83%
“…The consensus model of LOV signaling involves a light-driven Gln-flip in response to changes in flavin N5 protonation. [ 11 , 16 , 17 , 24 ] In most LOV structures, the conserved Gln residue occupies a buried conformation coplanar to the flavin isoalloxazine ring. In the dark state, N5 is unprotonated, with the active site Gln forming H-bonds to the N5 and O4 positions via its amide functionality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the side chain of the conserved glutamine may trigger -through a 1801 rotation after the H-transfer step -a process of structural changes by altering the hydrogen bond map of the protein. [5][6][7][8][9][10][11][12] The photocycle of LOV domains commences typically via a blue light trigger that excites the ground state flavin (S 0 ) rapidly to the singlet state (S 1 ) within femtoseconds (Fig. 2a).…”
Section: Introductionmentioning
confidence: 99%